Distinctive morphological characteristics of Fucus guiryi (Fucales, Phaeophyceae) from Canary Islands, subtropical eastern Atlantic Ocean - Ruiz-Medina, Marcos A.; González-Rodríguez, Águeda M.; Sansón, Marta (Phytotaxa, 2021)
The brown macroalgae in the order Fucales include foundation species on rocky habitats of temperate regions. This work focused on Fucus guiryi, a recently described species segregated from F. spiralis in a molecular basis. It inhabits the upper intertidal zone from the eastern North Atlantic to the subtropical Canary Islands, where is considered its southern limit. We examined morphology and anatomy of vegetative and reproductive structures of F. guiryi from the Canary Islands. Several distinctive characteristics in habit existed between F. guiryi and other species of the genus distributed northwards, such as length and width of stipe and branches, number of branches, and morphology and number of receptacles. Anatomical features reported here for the first time exhibited subtle differences with temperate F. vesiculosus, F. spiralis and F. serratus. The morphology and arrangement of medulla, cortex and meristoderm were also distinctive for F. guiryi. Mucilage in cellular interstitial spaces constitutes good evidence that explains the presence of F. guiryi at its warmest distribution limit in the Canary Islands.